(untitled) (Construction Economics and Building, 2024)
While initial costs in building economics cover a small portion of the costs incurred during its life-cycle, most occur in construction, operation, and subsequent processes. Despite its numerous contributions to building economics, the construction industry is slowly adapting to digital technologies. To overcome the barriers and crown the assets with their proper management, dynamic applications of digital tools and techniques of Industry 4.0 need to emerge in the construction industry. Therefore, this study aims to present an integrative approach that combines quantitative and qualitative analysis techniques to critically review the available literature on the potential contributions of digital construction technologies to building economics through the post-design phases of the life cycle. The primary focus of the investigation is how digital technologies can overcome prevalent problems and how they can impact building economics. The study contributes to the field by providing an awareness that will inform researchers and practitioners of the trends, gaps, and more profound exchange of ideas in future research efforts.